Structural study and molecular docking insights into laccase-mediated dye degradation - Yatindra Kumar; Hirdya Ramesh; Kalpana Dhabade; Manju Shahare; Bhawna Kalra (Sustainable Chemistry for the Environment)
Industrial wastewater often contains harmful dyes, posing significant environmental challenges. This study used computational tools to investigate the interactions between the low-degradability Azo dye, Reactive Blue 19, and laccase enzyme from two fungi species, Lentinus sp. WR2 and Trametes versicolor, as well as the protein Xyn5B (GH30) from Bacillus sp. BP7. Physiochemical characterization indicated acidic properties for Lentinus sp. WR2 and T. versicolor, while basic characteristics for Bacillus sp. BP7. Secondary structure (SOPMA analysis) revealed that most laccases had random coiling, enhancing protein flexibility. The negative GRAVY index revealed favorable water interaction for Lentinus sp. WR2 and Bacillus sp. BP7. The ERRAT plot validated the laccase 3D structure. The molecular docking results were compared using active site prediction and docking score. Lentinus sp. WR2 is linked with Reactive Blue 19 through a single residual amino acid THR 168; T. versicolor is linked through GLY 101, TRP 98, and TRP 512; and Bacillus sp. BP7 exhibited four linkages: VAL 262, TYR 263, TRP 117, and THR 260. The molecular docking results showed that Xyn5B demonstrated laccase activity and bound effectively with Reactive Blue 19, outperforming a commonly used fungal laccase in dye degradation. These findings enhance our understanding of enzyme-substrate interactions and highlight the potential of Xyn5B in eco-friendly dye degradation.